2012
DOI: 10.1038/jes.2012.55
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the vehicle contributions of metals to indoor environments

Abstract: A large number of diesel vehicles carrying gravel and sand shuttle back and forth every day on the major thoroughfares (Tai-16 and Tai-21) from Shinyi to Jiji in Nantou, Taiwan. A total of 10 stations along the major thoroughfares were selected as the exposure sites, whereas a small village located B9 km from a main traffic route was selected as the control site. Outdoor and indoor aerosol samples were collected using high-volume samplers and Harvard samplers, respectively. The metal concentrations of outdoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The PCA technique is one of the multivariate analyses that have been successfully applied for source identication. 6,27,51 PCA is adapted to quantitative variables, which transforms u possibly correlated variables into u uncorrelated variables, referred to as principal components. 52 PCA proposes to explain the maximum amount of variance with the fewest number of principal components (PCs) and minimum loss of relevant information.…”
Section: Statistical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCA technique is one of the multivariate analyses that have been successfully applied for source identication. 6,27,51 PCA is adapted to quantitative variables, which transforms u possibly correlated variables into u uncorrelated variables, referred to as principal components. 52 PCA proposes to explain the maximum amount of variance with the fewest number of principal components (PCs) and minimum loss of relevant information.…”
Section: Statistical Techniquesmentioning
confidence: 99%
“…Enrichment factors (EFs) have been widely used to distinguish between anthropogenic inuences and natural background View Article Online contents, 6,65,66 despite the intrinsic shortcomings associated with factors such as the variable composition of the local substrate or the impact of biogeochemical processes. 67 In this study, the EFs were used as screening tool to ascertain relevant PTEs to be included in the source apportionment study.…”
Section: Source Identication and Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Taiwan, several contaminants have been found in local soil and dust, such as heavy metals, 22,23 polycyclic aromatic hydrocarbons 24 and brominated flame retardants. 25 Young children may spend more time playing on the floor or horizontal surfaces and have a greater chance contacting soil and dust because of their unique pediatric activity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, young children might have a greater chance of contacting soil and dust which reside on the floor or horizontal surfaces, due to their unique pediatric activity patterns. Previous studies had shown that some contaminants such as heavy metals 44; 45 , polycyclic aromatic hydrocarbons 46 and brominated flame retardants 47 were found in soil and dust in Taiwan. Such pollutant concentration data are also helpful to estimate the parameters necessary for predicting the non-dietary exposures to contaminants in soil and dust, by young children living in Taiwan.…”
Section: Introductionmentioning
confidence: 99%